2013
DOI: 10.1039/c3ra43786h
|View full text |Cite
|
Sign up to set email alerts
|

Doubly-bridged PNP-lariat ethers and their complexes with silver(i) ions in methanol solution

Abstract: We report the preparation of four new double-bridged PNP-lariat ether derivatives L1-L4 synthesized from precursor 1 by the subsequent substitution of chlorine atoms. The process consists of two steps. In the first one two reactive chlorine atoms of the -PCl 2 exocyclic moiety are substituted with respective nucleophiles: 2,2 0 -thiodiethanethiol 2 and 2,2 0 -oxydiethanethiol 3. In the second step the other chlorine atoms are substituted by aziridynyl 6 and pyrrolidinyl 7 groups, respectively. Their structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
1
7
2
Order By: Relevance
“…Contrary to the previously-described PNP-lariat ethers derivatives [31][32][33][34] the sites and way of successive binding of silver ions (as confirmed by NMR and MS studies) were completely different. In the AgL system, the silver ion is bound by exocyclic nitrogen atoms derived from substituents (Scheme 4).…”
Section: Investigations Of Silver Ions Complexes With the Ligandcontrasting
confidence: 86%
See 3 more Smart Citations
“…Contrary to the previously-described PNP-lariat ethers derivatives [31][32][33][34] the sites and way of successive binding of silver ions (as confirmed by NMR and MS studies) were completely different. In the AgL system, the silver ion is bound by exocyclic nitrogen atoms derived from substituents (Scheme 4).…”
Section: Investigations Of Silver Ions Complexes With the Ligandcontrasting
confidence: 86%
“…Also here, the confirmation of the binding of the second silver ion is the NMR spectra (Figure 2c). The shifts of signals from the CH 2 OP group in the range of about 4 ppm are clearly visible and are similar to the ones previously described for such place of the silver ion binding [31][32][33][34]. In this stage of complexation, one can observe the shift of the signals located at about 3.30 ppm assigned to CH 2 -O fragments of the polyether ring.…”
Section: Investigations Of Silver Ions Complexes With the Ligandsupporting
confidence: 86%
See 2 more Smart Citations
“…These types of compounds form selective bindings with silver ions. 65,66 Additionally, recent investigations showed that silver compounds exhibit antibacterial properties. 67 It has been proved that the thiosubstituted PNP-lariat ethers are commonly used to remove highly toxic heavy metal pollutants and for recovery of silver from industrial wastes.…”
Section: Introductionmentioning
confidence: 99%